Toward smoke-free homes: A community-based study on initiatives of rural Indian women - Srabani Mittal; Samiran Das (Wolters Kluwer Medknow Publications, 2011)
Context: Since the home is the primary source of exposure of children to second-hand smoke (SHS), measures to restrict smoking at home should be introduced to protect children from its adverse health consequences. Aims: Objectives of the study were to assess the level of awareness of rural Indian women on the health impacts of SHS on children and to look into the strategies they used to reduce children's exposure to SHS at home. Materials and Methods: A community-based cross-sectional study was conducted among 438 rural women using a survey questionnaire. Information on socio-demographic characteristics, knowledge on specific health effects of SHS on children, and attitude toward having a smoke-free home were collected. The perceived reasons that made it difficult to have smoke-free homes were also explored. Results: A total of 75.8% of women agreed that SHS was a serious health risk for children. Knowledge on health impacts of SHS on children identified asthma as the most common problem. Smoking by husbands (89.7%) was the major source of exposure to SHS at home. While 67.6% of women reported having taken measures to limit SHS exposure in their homes, only 12.8% of them had tried to introduce a complete ban on smoking at home. On a five-point evaluation scale, 73.3% of the women indicated a failure of their initiatives to have smoke-free homes. Conclusions: Women's initiatives to introduce restrictions on smoking at home had very limited success and did not produce an appreciable change in smoking behavior at home. Lack of empowerment of women in rural India probably rendered the interventional measures ineffective.